Elaboración y comercialización de tabletas de café en el Ecuador - Arce Cali, Pareja Neira (2010)
Due to the different ecosystems that Ecuador has, to allow the coffee to make themselves across the country, reaching even grown in the Galapagos Islands, obtaining a high production capacity of coffee, making it one of the few countries in the world that exports almost all varieties of coffee, such as the Arabian washing, natural Arabic and Robusta. Due to the geographical location of Ecuador, their coffee is the best produced in South America and the most popular in Europe, like Cocoa. This project aims to identify the innovation needs of the consumer in the submission of coffee today, coffee comes in many presentations, but none is ready for use instantly, but rather should be done step by step and the traditional way. The method most suited to our project is the staff survey, which will take place at people aged between 18 and 65, because our target market surveys were conducted in supermarkets, cafes, cinemas, playgrounds food, offices, gas stations and sites with greater flow of people, they are made mostly in the city of Guayaquil, there will be a financial analysis to determine the profitability of the project, in order to determine the period in which to recover our investment, also will use financial indicators such as NPV and IRR, to know how profitable it is to the project, and finally we will have a sensitivity analysis to determine the variability that can exist in income